Flexibility measurement issues in supply chain management - Daniel Bauer; Martin Göbl (Journal of Applied Leadership and Management, 2017)
Research Question: The essential problem being analyzed in the present paper is the search for methods to assess or rather measure supply chain flexibility. Due to a multi-dimensional characteristic supply chain flexibility is particularly difficult to analyze and to evaluate with adequate performance measurement instruments as they are often ineffective qualitative frameworks or quantitative metrics that are limited in scope, non-inclusive or not significant enough. The question there-fore is whether there is a construct, a framework or any performance indicator that is capable of measuring supply chain flexibility adequately and that can be a benchmark; or is it necessary to develop an individual tool for a company because of its unique and special prerequisites to assess the flexibility of its supply chains? Methods: Most researchers and practitioners that investigated flexibility more on an inter-firm perspec-tive rather than relating it to supply chains. While having set the basis regarding the respective literature this paper follows a qualitative approach for the empirical analysis of the stated as-sumptions. Because of the exploratory character and the complexity of the subject expert in-terviews were conducted to get more in-depth insights and to derive conclusions concerning the correctness of the stated hypothesis. Results: The theoretical analysis combined with the empirical investigation came to the result that meas-uring supply chain flexibility could not be possible by using only one performance instrument or one metric and accredits that no single KPI can give an accurate statement whether a supply chain is flexible. Only a combination of several different KPIs would we capable and it is concluded that due to unique supply chain objectives, individual structures, processes and products there cannot be a real benchmark model for every existing supply chain.
Keywords: 650; Supply Chain Management; Supply Chain; Management; Logistics Management; Logistics